Respuesta :

x-2 /4 = 3x-2 /3

Cross multiply:

3(x-2) = 4(3x-2)

Simplify:

3x-6 = 12x -8

Subtract 3X from each side:

-6 = 9x -8

Add 8 to each side:

2 = 9x

Divide both sides by 9:

x = 2/9

Answer:

2/9 =x

Step-by-step explanation:

We can use cross products to solve this problem

x-2              3x-2

------------ = ----------

4                     3

3(x-2) = 4(3x-2)

Distribute

3x-6 = 12x-8

Subtract 3x from each side

3x-6-3x = 12x-8-3x

-6 = 9x-8

Add 8 to each side

-6+8 = 9x-8+8

2 = 9x

Divide by 9

2/9 = 9x/9

2/9 =x